Covalent mixing in the two-dimensional ferromagnet CrSiTe₃ evidenced by magnetic x-ray circular dichroism - Achinuq, B; Fujita, R; Xia, W; Guo, Y; Bencok, P; van der Laan, G; Hesjedal, T (Wiley, 2021)
The low-temperature electronic structure of the van der Waals ferromagnet CrSiTe3 has been investigated. This ferromagnetic semiconductor has a magnetic bulk transition temperature of 33 K, which can reach up to 80 K in single- and few-layer flakes. X-ray absorption spectroscopy (XAS) and x-ray magnetic circular dichroism (XMCD) measurements, carried out at the Cr L2,3 and Te Mb edges on in vacuo cleaved single crystals, give strong evidence for hybridization-mediated super-exchange between the Cr atoms. The observed chemical shift in the XAS, as well as the comparison of the XMCD with the calculated Cr L2,3 multiplet spectra, confirm a strongly covalent bond between the Cr 3d(eg) and Te 5p states. Application of the XMCD sum rules gives a non-vanishing orbital moment, supporting a partial occupation of the eg states, apart from the t2g. Also, the presence of a non-zero XMCD signal at the Te Mb edge confirms a Te 5p spin polarization due to mixing with the Cr eg bonding states. The results strongly suggest that superexchange, instead of the previously suggested single ion anisotropy, is responsible for the low-temperature ferromagnetic ordering of 2D materials such as CrSiTe3 and CrGeTe3. This demonstrates the interplay between electron correlation and ferromagnetism in insulating two-dimensional materials.